Heat transfer enhancement in a tube with combined conical-nozzle inserts and swirl generator - Promvonge, P.; Eiamsa-ard, S. (My University, 2006)
The enhancements of heat transfer characteristics in a uniform heat flux circular tube fitted with conical nozzles and swirl generator are experimentally investigated. In this research, the conical nozzles, assumed as a turbulator/reverse flow generator, are placed in a model pipe line through which air as working fluid is passed. Three different pitch ratios (PR) of conical-nozzle arrangements in the test tube are introduced with PR = 2.0, 4.0 and 7.0 in each run. In addition, the snail is also employed to provide swirling flow at the inlet of the test tube. It is found that each application of the conical nozzle and the snail can help to increase considerably the heat transfer rate over that of the plain tube by about 278% and 206%, respectively. The use of the conical nozzle in common with the snail leads to a maximum heat transfer rate that is up by 316%. Correlation equations for Nusselt number, friction factor and performance evaluation criteria to assess the real benefits in using the turbulators and swirl generator of the enhanced tube are determined. © 2006 Elsevier Ltd. All rights reserved.
Keywords: Conical nozzle; Friction; Heat transfer enhancement; Re-circulation; Reverse flow; Snail; Swirl flow; Turbulator